Direct comparison of visual and quantitative bone marrow FDG-PET/CT findings with bone marrow biopsy results in diffuse large B-cell lymphoma: does bone marrow FDG-PET/CT live up to its promise?. (October 2015) - Adams, Hugo JA; Kwee, Thomas C; Fijnheer, Rob; Dubois, Stefan V; Nievelstein, Rutger AJ; de Klerk, John MH
Background: Detection of bone marrow involvement using 18F-fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography (FDG-PET/CT) has been proposed as a non-invasive alternative to standard blind bone marrow biopsy (BMB) of the posterior iliac crest in patients with newly diagnosed diffuse large B-cell lymphoma (DLBCL). However, studies that directly compare FDG-PET/CT results with histopathology are currently lacking. Purpose: To directly compare both visual and quantitative bone marrow FDG-PET/CT to BMB at the right posterior iliac crest in patients with newly diagnosed DLBCL. Material and Methods: A total of 40 patients with newly diagnosed DLBCL, who had undergone FDG-PET/CT before BMB of the right posterior iliac crest, were retrospectively included. FDG-PET/CT images were visually assessed for bone marrow involvement in the right posterior iliac crest. 3D partial volume corrected mean standardized uptake value (cSUVmean ), maximum standardized uptake value (SUVmax ), and peak standardized uptake value (SUVpeak ) were measured in the right posterior iliac crest, using volume of interest analysis. BMB of the right posterior iliac crest was used as reference standard for bone marrow involvement. Results: Sensitivity and specificity of visual FDG-PET/CT analysis for the detection of bone marrow involvement in the right posterior iliac crest were 14.3% (95% confidence interval [CI], 0.5–53.4%) and 100% (95% CI, 87.6–100%), respectively. cSUVmean, SUVmax, and SUVpeak of BMB-negative patients (1.4 ± 0.49, 2.2 ± 0.69, and 1.7 ± 0.59, respectively) considerably overlapped with those of BMB-positive patients (1.8 ± 0.53, 2.7 ± 0.71, and 2.2 ± 0.61, respectively). Conclusion: In a local, head-to-head comparison with BMB, the diagnostic value of both visual and quantitative FDG-PET/CT for the detection of bone marrow involvement is low in patients with newly diagnosed DLBCL.